Using the Impact_Web_GIS_Platform to assess regional cohesion policy in promoting environmental sustainability in the CENTRE NUTS 2 of Portugal - Medeiros, E. (3rd PROFEEDBACK conference -Evaluation on Rural and Territorial Development, UrbanDevelopment, 2023)
This paper analyses the main impacts of the Operational Programme for Sustainability and Use of Resources (POSEUR 2014–2020), which is the most powerful EU Cohesion Policy mechanism implemented in Portugal concerning sustainable environmental development. The POSEUR interventions in Portugal aim at promoting sustainable development (Keeble, 1988) based on three axes: 1. The support of a transition to a model of the low-carbon economy; 2. The promotion of climate change adaptation strategies, risk prevention and management; 3. Protecting the environment and promoting the efficient use of resources.